Perceived Attitude of Farmers towards the use of ICT Tools among small holder rice farmers in Southeast, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study examined Perceived Attitude of Farmers towards the use of ICT Tools among small holder rice farmers in Southeast, Nigeria. Specifically, it described socioeconomic characteristics of smallholder rice farmers, ascertained the perceived attitude of farmers towards the use of ICT tools, analyzed the extent of use ICT tools and determined the significant relationship between smallholder rice farmers and their level of use of ICT. Data were collected with a structured questionnaire from 476 randomly selected smallholder rice farmers. Collected data were analyzed using descriptive statistics of mean threshold and Spearman Bivariate correlation. The result showed that smallholder rice farmers were relatively young because rice farming is physically demanding and old age can pose a problem to the cultural operations. It was discovered that the use of ICT tools is a source of motivation to both the extension agents and farmers’ thereby promoting learning, and ICT can be said to propel knowledge. The result on relationship between farmers and their level of use of ICT shows that a unit increase in farmer’s attitude will increase the level of use of ICT tools/format by 0.237 unit. It was recommended that government and other relevant bodies should ensure that ICT facilities are installed in rural communities, necessary trainings should be slated for smallholder rice farmers on the use of ICT tools/format by appropriate authorities to boost their confidence and reliance on ICT.
Keywords: Attitude; ICT use; Rice farmers; Southeast